SPECIAL ISSUE ON BIOSTATISTICS AND BIOMETRY IN THE ERA OF DATA SCIENCE - RODRIGUES, Paulo Canas; NAKAMURA, Luiz Ricardo; PEREIRA, Carlos Alberto de Bragança (Brazilian Journal of Biometrics, 2021)
This special issue of the Brazilian Journal of Biometrics (BJB) contains 16 papers. The main topic of the special issue is "Biostatistics and Biometry in the Era of Data Science", and it is the result of a collaboration between the BJB and the Brazilian Region of the International Biometric Society (RBras) in the sequence of the cancelled 2020 RBras annual meeting due to the COVID-19 pandemic.